UMP Joins Elite Club - T.N., Alagesh (The New Straits Times Press (M) Berhad, 2023)
KUANTAN: UNIVERSITI Malaysia Pahang (UMP) has joined the list of the world’s elite higher learning institutions after six subjects offered at the campus here were listed in the QS World University Rankings by Subjects 2023.